The Impact of Gadget Use on Students' Character at SDN 1 Danakerta - Evana Rizqoh; Sriyanto Sriyanto (UM Purwokerto Press, 2025)
The rapid technological advancement of the 21st century has significantly impacted various sectors of life, including education. One phenomenon that has emerged is the increasing use of gadgets among elementary school students, raising concerns about its effects on students' character development. This study aims to explore the influence of gadget use on the character of fifth-grade students at SDN 1 Danakerta. Using a descriptive qualitative approach, the study collected data through interviews with students, teachers, and parents, as well as direct observations of student behavior. The findings reveal that excessive gadget use negatively affects students' discipline, social skills, and empathy. Students who frequently use gadgets tend to have reduced peer interaction, lower social skills, and less adherence to academic tasks and school behavior rules. In response, both the school and parents have implemented strategies such as limiting screen time and encouraging more social interaction. This study emphasizes the importance of more structured management of gadget use both at school and at home and highlights the need for strengthened collaboration between parents and teachers to support positive character development in students.